Interventions to Prevent Potentially Avoidable Hospitalizations: A Mixed Methods Systematic Review - Lyhne, Cecilie Nørby; Bjerrum, Merete; Riis, Anders Hammerich; Jørgensen, Marianne Johansson (Frontiers in Public Health, 2022)
Background: The demand for healthcare is increasing due to an aging population, more people living with chronic diseases and medical comorbidities. To manage this demand, political institutions call for action to reduce the potentially avoidable hospitalizations. Quantitative and qualitative aspects should be considered to understand how and why interventions work, and for whom. The aim of this mixed methods systematic review was to identify and synthesize evidence on interventions targeting avoidable hospitalizations from the perspectives of the citizens and the healthcare professionals to improve the preventive healthcare services. Methods and Results: A mixed methods systematic review was conducted following the JBI methodology using a convergent integrated approach to synthesis. The review protocol was registered in PROSPERO, reg. no. CRD42020134652. A systematic search was undertaken in six databases. In total, 45 articles matched the eligibility criteria, and 25 of these (five qualitative studies and 20 quantitative studies) were found to be of acceptable methodological quality. From the 25 articles, 99 meaning units were extracted. The combined evidence revealed four categories, which were synthesized into two integrated findings: 1) Addressing individual needs through care continuity and coordination prevent avoidable hospitalizations and 2) Recognizing preventive care as an integrated part of the healthcare work to prevent avoidable hospitalizations. Conclusions: The syntheses highlight the importance of addressing individual needs through continuous and coordinated care practices to prevent avoidable hospitalizations. Engaging healthcare professionals in preventive care work and considering implications for patient safety may be given higher priority. Healthcare administers and policy-makers could support the delivery of preventive care through targeted educational material aimed at healthcare professionals and simple web-based IT platforms for information-sharing across healthcare settings. The findings are an important resource in the development and implementation of interventions to prevent avoidable hospitalizations, and may serve to improve patient safety and quality in preventive healthcare services. Systematic Review Registration: The review protocol was registered in PROSPERO https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020134652, reg. no. CRD42020134652.